EFFECTIVENESS IN THE USE OF SOFT AND MEDIUM TOOTHBRUSH BRISTLES WITH FONE’S TECHNIQUE FOR PLAQUE REDUCTION - Fennita Himawan; Isnur Hatta; Ika Kusuma Wardani (Dentino : Jurnal Kedokteran Gigi, 2020)
ABSTRACTBackground: Dental and oral hygiene of children in Indonesia is so alarming that serious awareness and attention are needed. Poor dental and oral hygiene is characterized by the presence of plaque deposits on tooth surface, forming an intercellular matrix that may instigate various dental and mouth problems. The prevalence of correct tooth brushing in Indonesia was very low at only 2.80%, in which South Kalimantan Province was 4.97% and Barito Kuala Regency was 3.55%. Objective: To determine the effectiveness of using soft and medium toothbrush bristles with fone’s technique to reduce plaque in students aged 10-11 years at SDN Berangas Timur 1, Barito Kuala Regency. Methods: The study used a true experimental method with a pretest-posttest with control group design consisting of pre-test and 8 post-test, and control group that was not given any treatment. Samples were randomly allocated by name sequence through simple random sampling technique of students aged 10-11 years at SDN Berangas Timur 1, Barito Kuala Regency. Inspection using PHPM plaque index was assessed on 6 index teeth. Research data were analysed using Mann Whitney's post hoc Friedman test. Results: The results for Friedman test in the treatment group showed p = 0.000. Mann Whitney test results in the treatment group with the control group showed p = 0.000 with a comparison of mean difference of 1.29 and 1.22 between the use of soft and medium toothbrush bristles with fone's technique. Conclusion: The use of soft toothbrush bristles with fone’s technique is the most effective in plaque reduction. Keywords : Effectiveness of brushing teeth, Fone’s technique, Plaque index, Soft and medium toothbrush dental